ПРЕНАТАЛЬНОЕ ВЛИЯНИЕ СИНЭСТРОЛА НА ДИНАМИКУ РОСТА ПОТОМСТВА - Сулайманова, Римма Тагировна; Выродов, Антон Сергеевич; Литвинова, Диана Даниловна; Вахитова, Диана Ильдаровна; Ахметова, Наиля Давлеталиевна; Акрамова, Элина Ринатовна (FORCIPE, 2022)